Método Pólya: una manera divertida de la enseñanza para la resolución de problemas matemáticos - Gonzalez Cabrera, Karla Lizbeth (2024)
The Pólya Method research: a fun way to solve mathematical problems has a general objective: contribute to the resolution of mathematical problems using the Pólya method in third year students at “VI Centenario” school; it is descriptive, mixed approach and quasi-experimental design; the theoretical framework addresses the variables: Pólya Method and Problem Solving; during the research process, the following methods were used: scientific, descriptive, analytical, synthetic and statistical; the collection of information was carried out through a diagnostic evaluation designed based on the contents of the curriculum of the third grade of basic education and an applied interview to the teacher, the investigated population includes twenty students and one teacher at “VI Centenario” school; the initial results demonstrate the necessity to undertake improvement actions for which the “Pólya Calcula” proposal was planned, the same one that was executed successfully, its effectiveness was confirmed with the second application whose captured data in a comparative table permits to visible significant changes. Therefore, it is concluded that the Pólya method is an interesting and effective tool for improving the teaching process to solve mathematical problems.